2009
DOI: 10.1182/blood-2008-10-178152
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of MHC II expression and transport in human plasmacytoid-derived dendritic cells

Abstract: Plasmacytoid predendritic cells (pDCs) play a key role in antiviral immunity through their capacity to produce large amounts of type I interferons in response to Toll-like receptor triggering, and to differentiate into dendritic cells (DCs). However, their antigen processing and presentation pathways remain poorly characterized. In this study, we analyzed major histocompatibility complex class II (MHC II) synthesis and transport in primary human pDCs. We show that stimulation of pDCs with influenza virus leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
3
24
0
Order By: Relevance
“…Examination of pDCs by confocal microscopy showed that all compounds colocalized with CpG-B in LAMP-1 ϩ CD63 ϩ HLA-DR ϩ endosomes, independently of their chemotype or labeling fluorophore. Our observations are in line with an elegant study by Sadaka et al 38 showing that MHC II molecules converge with LAMP-1 and CD63 (but not with TfR and EEA1 markers) in human pDCs treated with IL-3. LAMP-1 and CD63 are markers of late endosomes and lysosomes, whereas HLA-DR identifies MHC II molecules.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Examination of pDCs by confocal microscopy showed that all compounds colocalized with CpG-B in LAMP-1 ϩ CD63 ϩ HLA-DR ϩ endosomes, independently of their chemotype or labeling fluorophore. Our observations are in line with an elegant study by Sadaka et al 38 showing that MHC II molecules converge with LAMP-1 and CD63 (but not with TfR and EEA1 markers) in human pDCs treated with IL-3. LAMP-1 and CD63 are markers of late endosomes and lysosomes, whereas HLA-DR identifies MHC II molecules.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the vesicles where small molecule TLR7 agonists accumulate appear to belong to the MIIC. 20,38,39 Indeed, in pDCs, like in other antigen-presenting cells, the endolysosomal compartment is specialized for MHC II antigen presentation and is considered as a lysosome-related organelle. 39 The function of MHC II molecules is to access the endolysosomal network, bind peptides derived from the antigens, and display them on the cell surface to CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl6 has been shown to be down-regulated upon maturation of monocyte-derived DC (68); however, the functional interplay between these two transcriptional repressors in DCs has not been characterized. Finally, pDCs differ markedly from cDCs as they continually transcribe MHC-II genes even after antigen encounter (69,70). CIITA expression in this subset is driven primarily by CIITApIII.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CpGA stimulation of pDCs does not lead to the formation of MHC II intracellular clusters (51). CpGB-stimulated pDCs efficiently process and present CMV antigens and are capable of stimulating CMV-specific effector memory T helper cells.…”
Section: Figurementioning
confidence: 99%